KETERAMPILAN CALON GURU KIMIA DALAM MENGEMBANGKAN ALTERNATIVE ASSESSMENT - Hairida Hairida (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
The aim of this study was to investigate prospective chemistry teachers’ skills on developing alternative assessment. Students of chemistry program of FKIP Untan participated on this study. They had already taken PPL-2 class on academic year of interview guidelines and observations sheets were used to collect data. This study showed that prospective chemistry teachers’ skills on developing traditional assessment (essay and multiple choice test) was categorized as good. On the other hand, prospective chemistry teachers’ skill on developing alternative assessment was categorized as fair. The biggest obstacle teachers had on developing alternative assessment was to make and design task and rubric assessment, and how to implement alternative assessment on learning process.AbstrakPenelitian ini untuk menyelidiki keterampilan calon guru kimia FKIP Untan Pontianak dalam mengembangkan alternative assessment melalui studi deskriptif. Subyek penelitian ini adalah   mahasiswa program studi Pendidikan Kimia yang mengambil mata kuliah PPL-2 Tahun Akademik 2016/2017 dengan alat pengumpul data  berupa  pedoman wawancara dan lembar pengamatan disertai rubrik penilaian yang disusun berdasarkan aspek keterampilan dalam mengembangkan alternative assessment. Hasil penelitian menunjukkan sebanyak 97,67% calon guru kimia terampil dalam mengembangkan penilaian tradisional (bentuk pilihan ganda dan uraian),   dan sebanyak 74% calon guru kimia terampil dalam  mengembangkan alternative assessment. Kendala terbesar calon guru kimia FKIP Untan dalam mengembangkan alternative assessment adalah membuat task dan rubrik penilaian.